Development of discovery learning-based e-module in islamic-integrated protist subject in madrasah aliyah - Salma Nada Laila; Nanik Lestariningsih; Mukhlis Rohmadi (JPBIO (Jurnal Pendidikan Biologi), 2022)
Discovery learning-based e-module in Islamic-integrated protist subject is a teaching material innovation that becomes a solution to problems in learning process and is generated from the results of a need analysis on teachers and Grade 10 students. The developed e-module is important to study to find out the validity and attractiveness level of a product. The research method employed is the research and development (R&D) with ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The e-module validity test is carried out by 5 experts (2 material experts, 2 media experts, and a tafsir expert, whereas, the attractiveness test was conducted by a Biology teacher and Grade 10 students at MA Muslimat NU. Based on the result of the final stage of the validation, the developed e-module is valid with an average value (material expert = 3.46, media expert = 3.81, and tafsir expert – 3.79). The e-module attractiveness test by teachers generates an average value of 3.25 within a criterium of “very interesting”. Additionally, the result of students’ assessment of the e-module attractiveness resulted in an average value of 3.23 or within the “interesting” criteria.